2018
DOI: 10.1177/1089253218785362
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes Associated With Sepsis After Coronary Artery Bypass and Open Heart Valve Surgeries

Abstract: We identified multiple patient and surgical characteristics as well as postoperative outcomes associated with postoperative sepsis development in the high-risk population of patients undergoing cardiac surgery. Early identification of patients who are at high risk for postoperative sepsis can facilitate early treatment interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
6
0
1
Order By: Relevance
“…In the current study, one patient was admitted to the infection service due to postoperative sepsis, and one female patient developed an abortion after vaginal bleeding. Sepsis was one of the complications observed after cardiac surgery (3). In a study, sepsis was reported in 1.9% (n=2) of the patients after valve surgery (n=23) (2).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the current study, one patient was admitted to the infection service due to postoperative sepsis, and one female patient developed an abortion after vaginal bleeding. Sepsis was one of the complications observed after cardiac surgery (3). In a study, sepsis was reported in 1.9% (n=2) of the patients after valve surgery (n=23) (2).…”
Section: Discussionmentioning
confidence: 98%
“…Patients with mechanical heart valve surgery should be followed up in terms of the prosthetic valve and open heart surgery-related complications. In the long term, complications, such as heart failure, infective endocarditis, sternal wound infections, neurological complications, valve-related complications, acute renal failure, and sepsis can be observed due to open-heart surgery (2,3). Following these complications, problems, such as valve thrombosis, thromboembolism, and bleeding, may occur with mechanical prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Снижение уровня альбумина в большей степени свидетельствует о системном воспалении и мало зависит от нутритивного статуса, как принято полагать [42]. Так, по данным разных авторов, уровни альбумина при сепсисе [43][44][45] и ВГФС [46][47][48] сходны, при этом во всех работах отмечено ухудшение прогноза у пациентов с гипоальбуминемией. С-реактивный белок и прокальцитонин являются маркерами как воспаления в целом, так и бактериальной инфекции в частности [49,50].…”
Section: рис 3 корреляционный анализ концентрации общего и гликозилunclassified
“…In fact, high APACHE II, SAPS and SOFA scores, acute kidney injury and sepsis in the early postoperative period, which can actually lead to an increased fluid balance, have been associated independently with increased risk of early deaths after cardiac surgery. [6][7][8] In our opinion, no matter how refined the adjustment is for differences in early postoperative conditions, it is never possible to ensure a complete adjustment for differences between non-survivors and survivors. Furthermore, postoperative fluid balance has been significantly associated with increased risk of acute kidney injury after cardiac surgery.…”
Section: Sirmentioning
confidence: 99%